Relative Effects of Practical and Project Based Learning on Students’ Interest in Biology in Aguata Education Zone - Enebechi, Regina Ijeamasi; Ezenwafor, Chiamaka Elizabeth (Education and Development Research, 2026)
The study investigated effects of practical and project based learning on students’ interest in Biology in Aguata Education zone of Anambra State, Nigeria. Two research questions and three hypotheses guided the study and relevant literatures were also reviewed. The study adopted quasi-experimental design. The population of the study comprised of 1098 SS 2 Biology students. The sample consisted of 105 SS2 students (57 males and 48 females). The sample was obtained using multi-stage sampling procedure. Academic Interest Scale for Adolescent adapted from Luo et al (2019) was used as instruments for data collection. The instrument was subjected to face and content validation. AISA reliability was established using Cronbach alpha and reliability coefficient yielded 0.74. Mean and Standard Deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The study revealed that students in the practical based learning group developed better interest than those taught the same Biology concept using project based learning. The study also observed that female students developed better interest than their male counterpart in the use of practical based learning in the Biology concepts taught. From the findings it was concluded that practical based learning boosts interest in Biology subject. Also, gender differences are nuanced, but no significant in gender instruction interactions. From the conclusions, implication was that stake holders should advocate for universal, equitable and varied instructional strategies.